Behavior of Simply Supported Concrete Beam Using CFRP (Carbon Fiber Reinforced Polymer). Issue 1 (November 2021) - Shivankar, Akshay; Dabhekar, K.R.; Patil, P.B.; Mase, D.P.; Khedikar, I.P.
Abstract: The aim of this paper is to study the behavior of beam with the use of CFRP composite by experimentally and by ANSYS and compare both the results and compare load carrying capacity. For experimentally we cast Nine no's of beam of size 100×100×400 mm, of M30 grade of concrete and curing for 7 days and after 7 days curing we conduct UPV test and find homogeneity of concrete beam and decided carbon fiber wrapping techniques we create two set of beam with 230 GSM wrapped with double layer and two set of beam with 430 GSM wrapped with double layer and two set of beam with 430 GSM wrapped with single layer, and 3 control beams without wrapping and test for flexural strength and by this test we observe the ultimate load carrying capacity and flexural strength of carbon fiber wrapped beam is increased as compare to control beams.